The UN Food Systems Summit 2021: Lessons of the gender and finance levers - Díaz-Bonilla, Eugenio; McNamara, Brian; Njuki, Jemimah; Swinnen, Johan; Vos, Rob (International Food Policy Research Institute, 2023)
The United Nations Food Systems Summit, aimed to move food systems transformation to the top of the global policy agenda. An important element of the discussions were the “levers of change,” cross-cutting areas of work for food systems transformation. This paper reviews the operation of two levers: gender and finance. It analyzes the main debates and implementation issues related to mainstreaming gender dimensions and to leveraging finance for food system transformation. Using a political-economy framework of analysis, the paper draws conclusions for global food system governance and the likelihood of the UNFSS agenda for action to succeed.